Peningkatan Keterampilan Menulis Surat Pribadi Dengan Pendekatan CTL Pada Siswa Kelas VII SMPN 1 Beringin - Atikah Supiyah Ansoriyah; Rindy Antika; Safnah Sagala; Mustika Wati Siregar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is a type of classroom action research (PTK) which uses a qualitative approach. The CTL (Contextual Teaching and Learning) approach is the approach used in this research. The research subjects were students in class VII-2 of Beringin 1 State Junior High School in the 2023/2024 academic year, consisting of 32 students, namely 13 boys and 19 girls. Data collection techniques include objective tests, observation, direct question and answer, documentation, and field notes. The instruments used include learning outcomes tests, assessment of students' attitudes and emotions, assessment of writing skills based on assignments, as well as observation sheets from the research process. The results of reflection and data analysis during cycles I and II of the learning process show that the implementation of CTL has gone well. Students are very involved in learning activities and most have completed assignments. The indicators for implementing learning using the CTL method in cycle II entered the very good category or 90.